Using genetically encoded calcium indicators to study astrocyte physiology: A field guide - Lohr, Christian; Beiersdorfer, Antonia; Fischer, Timo; Hirnet, Daniela; Rotermund, Natalie; Sauer, Jessica; Schulz, Kristina; Gee, Christine E. (Frontiers in Cellular Neuroscience, 2021)
Ca2+ imaging is the most frequently used technique to study glial cell physiology. While chemical Ca2+ indicators served to visualize and measure changes in glial cell cytosolic Ca2+ concentration for several decades, genetically encoded Ca2+ indicators (GECIs) have become state of the art in recent years. Great improvements have been made since the development of the first GECI and a large number of GECIs with different physical properties exists, rendering it difficult to select the optimal Ca2+ indicator. This review discusses some of the most frequently used GECIs and their suitability for glial cell research.